2011
DOI: 10.3852/11-027
|View full text |Cite
|
Sign up to set email alerts
|

ITS-1 versus ITS-2 pyrosequencing: a comparison of fungal populations in truffle grounds

Abstract: In a recent study pyrosequencing of the ribosomal internal transcribed spacer-1 (ITS-1) has validated the effectiveness of such technology in the survey of soil fungal diversity. Here we compare the two ITS regions, ITS-1 and ITS-2, of the fungal populations occurring in Tuber melanosporum/Quercus pubescens truffle grounds and sampled in two areas, one devoid of vegetation (''burned'', brulé in French) where T. melanosporum fruiting bodies are usually collected, and outside the brulé. TS1F/ITS2 and ITS3/ITS4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 25 publications
9
105
0
Order By: Relevance
“…Previous studies have indicated the dominance of Ascomycota in truffle grounds (Mello et al, 2011) and in the rhizosphere of Xinjiang Jujube (Liu et al, 2015). Zygomycota was the second dominant phylum, which has also been reported as sub-dominant species in the Negev desert (Bates et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated the dominance of Ascomycota in truffle grounds (Mello et al, 2011) and in the rhizosphere of Xinjiang Jujube (Liu et al, 2015). Zygomycota was the second dominant phylum, which has also been reported as sub-dominant species in the Negev desert (Bates et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patterns observed at a given level of taxonomic discrimination might not be found at lower or higher levels [5,7,14]. Studies on the diversity of soil fungal communities carried out so far by means of NGS have either focused on a phylogenetically restricted set of taxa (e.g., arbuscular mycorrhizal fungi [31][32][33][34]) or have been performed on a restricted (local or regional) spatial scale (e.g., [21,[35][36][37][38][39][40][41][42][43][44]). To bridge the gap between local and wide-scale assessments, additional studies are required, encompassing greater spatial sampling across multiple soil biomes.…”
Section: Introductionmentioning
confidence: 99%
“…The isolates from Mohlaba cross and Dan village appeared as independents. The size of the ITS2 region and the G-C content of A. bataticola corresponds to those reported in other studies [13,41]. Clustering patterns produced with the RAPD data ( Fig.…”
Section: Its2 Sequences Analysismentioning
confidence: 67%